Postoperative recurrence and systemic metastasis of large cell neuroendocrine carcinoma of the breast: a case report including T-DXd treatment - Zhu, Siying; Qu, Yinxi; Chen, Dong; Luo, Xiaomao (Frontiers in Oncology, 2026)
We report a rare case of large-cell neuroendocrine carcinoma (LCNEC) of the breast in a 49-year-old woman. The patient presented after discovering a right breast mass five years earlier. Mammography revealed a high-density mass and enlarged axillary lymph nodes. Biopsy confirmed invasive carcinoma with neuroendocrine differentiation. Initially, she received TE chemotherapy, followed by carboplatin and etoposide (CBP) due to disease progression. After eight cycles, she underwent modified radical mastectomy and postoperative radiotherapy. One year later, the patient developed metastases in the liver and bones, with a liver biopsy confirming recurrent LCNEC. Given the aggressive nature of the disease, trastuzumab deruxtecan (T-DXd) was initiated on October 11, 2025. Follow-up imaging demonstrated significant reduction in hepatic and peritoneal metastases, with partial response (PR) as the best observed response. Treatment with T-DXd is ongoing, highlighting its efficacy in managing aggressive LCNEC with distant metastasis.